2008
DOI: 10.4049/jimmunol.181.11.8162
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Complement Activation on Antigen Microarrays Generates Functional Antibody Profiles and Helps Characterization of Disease-Associated Changes of the Antibody Repertoire

Abstract: Humoral immune responses are traditionally characterized by determining the presence and quality of Abs specific for certain Ags. Arraying of large numbers of Ags allows the parallel measurement of Abs, generating patterns called Ab profiles. Functional characterization of these Abs could help draw an even more informative map of an immune response. To generate functional Ab profiles we simultaneously tested not only IgM, IgG, and IgA binding to, but also complement activation by, a panel of endogenous and exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
(25 reference statements)
1
12
0
Order By: Relevance
“…Experimental data, in agreement with the expectable correlations [15] suggested that it is mostly IgM and IgG that determines complement depositions to self antigens. Detection of these two classes of immunoglobulins seems inevitable in order to interpret effector functions.…”
Section: Description Of Immune Complex Content On a Population Level:supporting
confidence: 80%
“…Experimental data, in agreement with the expectable correlations [15] suggested that it is mostly IgM and IgG that determines complement depositions to self antigens. Detection of these two classes of immunoglobulins seems inevitable in order to interpret effector functions.…”
Section: Description Of Immune Complex Content On a Population Level:supporting
confidence: 80%
“…The CF titer increased significantly at 4 weeks following priming with c-RBC in local compared to that of the Saanen does (p<0.05); however, the difference in CF titers was insignificant at 3 weeks following boosting (p>0.05). The reasons for the difference in the CF titer following priming in locals versus Saanen does will be the subject of future investigations due to the importance of CF in amplification of the humoral responses (Paul 2008), in chemotaxis (Meyers 2007) and anaphylatoxic shocks (McEwen 1992;Decker 2000;Papp et al 2008), and in opsonization (Rooijakkers et al 2005;Paul 2008). …”
Section: Resultsmentioning
confidence: 98%
“…First, we asked whether our patients' anti-NY-ESO-1 or anti-SSX-2 antibodies, which reacted not only with the respective recombinant proteins but also recognized antigen endogenously expressed by tumor cell lines (Supplementary Figure 3C) were in principle able to directly activate the complement system. Assessing the activation of the classical complement pathway by serum antibodies [10], we found for the first time, both CTA-specific antibodies to be potent inducers of the complement system, as evidenced by C3-deposition on a membrane coated with recombinant protein (Fig. 2a).…”
Section: Cta-specific Antibodies Are Capable Of Promoting Complement mentioning
confidence: 98%
“…Proteins were blotted and membrane treated as outlined above. As described by Papp et al [10], this deposit can be detected on nitrocellulose membranes by a C3-specific antibody. Human serum was diluted 1:5 and incubated for 3 h on the nitrocellulose membrane at room temperature prior to stringent washing.…”
Section: Complement Activationmentioning
confidence: 99%